Julia Margaret Cameron : the complete photographs - Cameron, Julia Margaret; Cox, Julian; Ford, Colin (2003)
This volume is a biography and comprehensive, annotated listing of all the known works of British photographer Julia Margaret Cameron (1815-1879). Cameron became known for her portraits of celebrities of the time, and for photographs with Arthurian and other legendary or heroic themes. Although her style was not widely appreciated in her own day, her work has had an impact on modern photographers, especially her closely cropped portraits. In addition to a complete catalog of Cameron's photographs, there is information on her life and times, initial experiments, artistic aspirations, techniques, small-format images, albums, commercial strategies, sitters, and sources of inspiration. Also provided are a selected bibliography of publications on Cameron, a list of exhibitions of her work held both in her time as well as our own, and a summary of important collections where her pictures can be found.